Glutathione peroxidase responses in mature horses following the withdrawal of an organic selenium supplement - G. Bertin (Italian Journal of Animal Science, 2010)
The study comprised 25 mature horses and incorporated five dietary treatments; a negative control (C: 0.085 ppm of Se in the diet), 3 levels of organic Se supplementation (S2, S3 and S4; 0.2, 0.3 and 0.4 ppm of Se on DM respectively) and one positive control supplemented with Na selenite (N3: 0.3 ppm of Se on DM). Diets were offered for 112 days (supplementary period) after which horses were blood sampled to determine GSH-Px activity. Sampling was repeated at 28 day intervals for the following 112 days (post-supplementary period). Increased GSH-Px activity was observed with ascending concentrations of dietary Se following the supplementary period. GSH-Px activities are still notably higher at the end of the post-supplementary period in S2, S3, S4 and N3 when compared to C, although rates of decline were greatest in those treatments with the highest levels of selenium supplementation. Furthermore, GSH-Px activity was better maintained in those animals that had received organic Se following the withdrawal of Se supplements. Therefore, from a nutritional viewpoint, organic forms of Se are superior to selenite as GSH-Px activity is maintained during periods of Se inadequacy.